Female Employment and Structural Transformation - Moritz Kuhn; Iourii Manovskii; Xincheng Qiu (Institute of Labor Economics (IZA), 2024)
Two prominent secular trends characterize the transformation of labor markets in industrialized countries in recent decades. First, employment has shifted from manufacturing to services. Second, the share of female employment in total employment has risen sharply. This paper documents a novel fact linking these two trends: female employment shares within manufacturing and within services have remained virtually constant over time and across developed economies. Constant sectoral gender shares imply that an exogenous increase in female labor supply can by itself induce structural change. We provide empirical evidence for the presence of this effect in the data. We then propose a quantitative theory of structural change with nonhomothetic preferences, differential sectoral productivity growth, gender complementarity in sectoral production, and rising female employment, and calibrate it to the U.S. economy. Quantitatively, we find that the rise in female employment accounts for about two-thirds of structural change in the U.S. over the past five decades.
Keywords: 330; structural change; female employment; labor markets